2016
DOI: 10.5935/0103-507x.20160065
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor paradox in the occurrence of cardiac arrest in acute coronary syndrome patients

Abstract: ObjectiveTo compare patients without previously diagnosed cardiovascular risk factors) and patients with one or more risk factors admitted with acute coronary syndrome.MethodsThis was a retrospective analysis of patients admitted with first episode of acute coronary syndrome without previous heart disease, who were included in a national acute coronary syndrome registry. The patients were divided according to the number of risk factors, as follows: 0 risk factor (G0), 1 or 2 risk factors (G1 - 2) and 3 or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In-hospital mortality and complications were showed little higher trend in patients with risk factors, but there was not statistical significance. This finding is consistent with the previous studies [13,14,17]. Canto et al [14] reported that among patients with incident AMI without prior CV, in-hospital mortality was inversely related to the number of coronary heart disease risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…In-hospital mortality and complications were showed little higher trend in patients with risk factors, but there was not statistical significance. This finding is consistent with the previous studies [13,14,17]. Canto et al [14] reported that among patients with incident AMI without prior CV, in-hospital mortality was inversely related to the number of coronary heart disease risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Rosa et al 9 recently investigated the impact of pre-existing comorbidities and conventional risk factors on the outcome of patients admitted with their first episode of AMI. 23,24 The authors found that the absence of any established cardiovascular risk factor was independently associated with the development of CA.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In this regard, recently reported data demonstrated that especially young patients presenting with fewer cardiovascular comorbidities are at higher risk of CA in the acute phase of AMI, which indeed underlines a strong need to elucidate the prognostic relevance of CA from an age-specific perspective. 9 While the impact of CA on both mortality and neurological outcomes poses a well investigated field during the past decades, there is lack of evidence on its age-specific prognostic impact independently from an AMI perspective. 10 However, suitable age-specific secondary prevention and risk-stratification seems of utmost importance, especially in premature AMI individuals, rather losing decades of life expectancy than years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation